The Effect Of Stem Project-Based Learning On Self-Efficacy In Learning Physics, Scientific Reasoning, And Achievement In Physics Mechanics Test Among Form Four Secondary School Students - Jamali, Seyedh Mahboobeh (2018)
This research aimed to study the effect of STEM project-based learning (PjBL) teaching methods on self-efficacy in learning physics, scientific reasoning and achievement in physics mechanics test among Form Four secondary-school students. The sample consists of two groups of students, with 50 students being exposed to the STEM PjBL teaching method (experimental group), and 57 students the conventional teaching method (control group). The study employed a quasi-experimental methodology with a pre-test and post-test design. To analyze the collected data both descriptive and inferential statistics such as multivariate analysis of covariance (MANCOVA) were utilized. The results revealed that the STEM PjBL method significantly improves self-efficacy in learning physics, scientific reasoning, and achievement in physics mechanics test among the participants of the study compared to the conventional teaching method. It was discovered that the STEM PjBL teaching method (experimental) group (M = 14.54, out of 20) performed significantly better than the conventional teaching method (control) group (M = 9.38, out of 20), F (1, 102) = 86.36, P < .0167 in the post-test results of physics mechanics achievement test. Therefore, there was a 25.80% improvement on the post-test results of the students’ achievement in physics mechanics test scores, between students who were exposed to STEM PjBL compared to those who were instructed using conventional teaching methods.